The Factors Associated with Successful Aging in Elderly: A Systematic Review - Inta Susanti; Glorya Riana Latuperissa; Fathmy Fitriany Soulissa; Anis Fauziah; Tintin Sukartini; Retno Indarwati; Arifal Aris (Universitas Airlangga, 2020)
Introduction: Successful aging (SA) is defined as adding life to years and as feeling satisfied with past and present life. Criteria for successful aging: free of disease and disability; high levels of physical and cognitive functioning; and social engagement. The aim of this study was to describe factors associated with successful aging among older peopleMethods: The literature search strategy identified 1.914 articles. The PRISMA strategy was used to identify articles that met inclusion criteria. Initially 255 duplicated studies were excluded; resulting in 1659 articles screened for inclusion in this review. A further 1567 articles were removed based on the title and abstract. The remaining 32 articles were assessed for inclusion this review. Nineteen articles were excluded. In total 13 studies met inclusion criteria for this review. These 13 studies were assessed for quality, data extraction and synthesis.Results: The factors associated with successful aging are age, gender, few physical morbidities, absence of depression, body weight or BMI in the overweight range, carrying out more than six AADL and high levels of physical activity, education, smoking, alcohol consumption, marital status, proactive engagement, wellness resources, positive spirit, and valued relationships, sleep quality, leisure activity, economic status, religious activity, and high perceived meaningfulness.Conclusion: The factors that influence successful aging are socio-demographic factor, physiological, psychological, and lifestyle behavioral factors. This study shed light on the key factors that healthcare providers or researchers should consider in intervention studies and programs to promote healthy aging.